Challenges in Using the Posterior Inferior Cerebellar Artery for Revascularization of the Anterior Inferior Cerebellar Artery: A Microsurgical Anatomic Study - (:unkn) unknown (ELSEVIER SCIENCE INC, 2021)
BACKGROUND: A bypass is usually required to prevent ischemia during the treatment of anterior inferior cerebellar artery (AICA) aneurysms. The intracranial (IC)-to-IC bypass provides several advantages over the extracranial-to-IC bypass in the posterior fossa. However, there are only 2 case reports about AICA revascularization with the posterior inferior cerebellar artery (PICA). We aimed to investigate the microsurgical anatomical challenges for PICA to AICA anastomosis. METHODS: Ten cadaveric heads injected with colored silicone were inspected on both sides using a lateral transcondylar approach. After the donor and recipient arteries were examined from the posterior side, neurovascular contents of the posterior fossa were excised and the origin, course, and variations of both arteries were investigated from the anterior view. The diameters of the AICA and PICA segments and the intersegment distance were measured. RESULTS: PICA variations and posteromedial origins from the vertebral artery were identified in 8 of the 20 right and 6 of the 20 left sides, and the first segment of the PICA was not present in 7 sides. Furthermore, in 18 sides, the PICA was trapped between the lower cranial nerves and dentate ligaments. Therefore the donor artery could not be brought closer than 1 cm to the recipient artery in 19 sides. Moreover, AICA variations were identified in 6 sides, and in 12 sides, the diameter of the recipient artery was <1 mm. CONCLUSIONS: The mostly PICA-related issues made PICA-to-AICA anastomosis unfeasible in all cadaveric heads included in the study.
Keywords: Anastomosis; Anterior inferior cerebellar artery; Bypass surgery; Ischemia; Microneurosurgical anatomy; Posterior inferior cerebellar artery; Revascularization; OCCIPITAL ARTERY; ANEURYSMS; BYPASS; ANASTOMOSIS; FUTURE; ORIGIN